A historiography of South Africa's public health care governance affecting health system strength from the 1940s to 2023 - Martin, Jade (School of African and GenderStuds, Anth and Ling, 2025)
Segregationist minority rule socially engineered a system built on the brutality of black and brown people in South Africa leading to the aggravation of opportunistic infections. Centuries of white capitalist governance enslaved Black populations through settler colonialism and continued to inflict violence through the apartheid regime. Circulatory migrant labour and various forms of racist economic, health and land policies entrenched deliberate social disintegration in the country. The political economy formalised the maldistribution of health by ensuring the expansion of debilitating diseases like tuberculosis (TB) and HIV/AIDS throughout the twentieth century. Systemic violence by state government structures exploited Black vulnerabilities through the demonstration of structural violence. This shows how government-sanctioned policies affect not only health institutions within health systems, but also in wider constructions of power and health inequalities in South Africa. So, the unequal distribution of life-threatening diseases were contingent on the racialised dimensions of state power that impacts our contemporary health system. After the materialisation of democracy, scepticism arose toward the ANC's ambitious and unstable re-articulation of social justice and equity, particularly in its propulsions for development and economic growth. In some way, this offers a retrospection on the ANC-led public health system and their shortfalls in redressing deep-rooted health inequities since the injection of systemic racism. In the thesis, I provide openings to question the strength of South Africa's health system through an assemblage of the Health Systems Research and the Health Humanities. These linkages deepen the scholarship and relationship between subjectivities (experiences) of health and the connections to public health legislature among its regulatory bodies. I navigate the histories of the colonial and apartheid public health systems through to the advent of liberation to consider how layers of structural violence plague negative experiences of health, and factors inhibiting access to health facilities and efficient treatment. Engaging with Foucault's theorisation on governmentality is necessary to frame a critique of the structure and scope of state power and its role in the regulation of health. The effects of neoliberal policies directly inspired transnational activism during the HIV/AIDS epidemic by compromising the fundamental freedoms and rights to health outlined in South Africa's Constitution. The thesis thus concentrates on neoliberalism as practiced during apartheid and post-apartheid contexts which has prominently targeted marginalised and vulnerable populations within the wider arrangements of globalisation and global public health. To do so, the project illustrates how democratic governance and health systems designed in South Africa are inextricably connected to neoliberalism which affects the potential for liberatory, equitable and transformed iterations of health care. Therefore, the thesis aims to contribute to the growing literature on health systems research and the health humanities through the construction of a historical account of the public health care system and its impact on the implementation of equitable programs for health and improved health outcomes provincially.